Upaya Meningkatkan Hasil Belajar Tematik Tema 2 Subtema 1 melalui Pemanfaatan Modul Pembelajaran pada Siswa Kelas V SDN 3 Bandar Mataram Lampung Tengah - Joko Susanto (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2021)
This study aims to find out how to improve thematic learning outcomes of theme 2 subtheme 1 through learning modules for fifth grade students of SD Negeri Bandar Mataran, Central Lampung. This type of research is Classroom Action Research. The results of this study indicate an increase in student learning outcomes during the learning process using learning modules, namely: (a) Learning in Cycle I obtained an average score of student activity of 2.2 (enough); (b) While in the learning in Cycle II, the average score of student activity was 3.8 (good). Collaborative work in classroom action research can be used as a vehicle for learning. Through collaborative work, classroom teachers will have an overview of effective theoretical learning, because classroom action research is based on concrete problems so that teachers are the best able to do it.